2005
DOI: 10.1016/j.neuroimage.2004.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Modelling event-related responses in the brain

Abstract: The aim of this work was to investigate the mechanisms that shape evoked electroencephalographic (EEG) and magneto-encephalographic (MEG) responses. We used a neuronally plausible model to characterise the dependency of response components on the models parameters. This generative model was a neural mass model of hierarchically arranged areas using three kinds of inter-area connections (forward, backward and lateral). We investigated how responses, at each level of a cortical hierarchy, depended on the strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
257
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 277 publications
(264 citation statements)
references
References 64 publications
7
257
0
Order By: Relevance
“…In this state, representations of alignment keys (Ullman, 1996), candidate object models, or object parts are activated. Later during the N350, this occipito-temporal cortex is active again, but this time performing the higher-order neural computations, involving recurrent and feedback interactions within these areas and with other areas, such as ventrolateral prefrontal cortex (Brincat & Connor, 2006;David, Harrison, & Friston, 2005), that support more sophisticated cognitive abilities with objects (Kosslyn et al, 1994), as well as implicit object memory (Schendan & Kutas, 2003) and perhaps familiarity (Curran et al, 2002). This state enables activation of the detailed visual knowledge required for the object model selection or model verification processes involved in abilities, such as basic level categorization of an object into a known class (e.g., dog, car, cup) or identification of individual objects like your cat or his bat (Ganis, Schendan, & Kosslyn, 2007;Lowe, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In this state, representations of alignment keys (Ullman, 1996), candidate object models, or object parts are activated. Later during the N350, this occipito-temporal cortex is active again, but this time performing the higher-order neural computations, involving recurrent and feedback interactions within these areas and with other areas, such as ventrolateral prefrontal cortex (Brincat & Connor, 2006;David, Harrison, & Friston, 2005), that support more sophisticated cognitive abilities with objects (Kosslyn et al, 1994), as well as implicit object memory (Schendan & Kutas, 2003) and perhaps familiarity (Curran et al, 2002). This state enables activation of the detailed visual knowledge required for the object model selection or model verification processes involved in abilities, such as basic level categorization of an object into a known class (e.g., dog, car, cup) or identification of individual objects like your cat or his bat (Ganis, Schendan, & Kosslyn, 2007;Lowe, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…(1) Biophysically realistic models of neural networks that explicitly simulate causal interactions between populations of cortical neurons (David et al, 2005) . Tested models.…”
Section: Basic Principles Of Dcmmentioning
confidence: 99%
“…2a). The generative model of DCM for MEG/EEG (David et al, 2005) combines the Jansen model (Jansen and Rit, 1995), a neural-mass model originally developed for explaining visual responses, with rules of cortical-cortical connectivity derived from the analysis of connections between the different cortical layers in the visual cortex of the monkey (Felleman and Van Essen, 1991). In the Jansen model, a cortical area is modeled by a population of excitatory pyramidal cells, receiving (i) inhibitory and excitatory feedback from local (i.e., intrinsic) interneurons and (ii) excitatory input from neighboring or remote (i.e., extrinsic) areas.…”
Section: Basic Principles Of Dcmmentioning
confidence: 99%
“…First, from a methodological point of view, we have shown that hidden neural activity (i.e., activity that is not recordable using noninvasive methods) can be recovered using parameter estimation of biophysical models of brain networks (dynamic causal modeling) (David et al, 2005. Second, the present data allow us to make specific inferences on subcortical-cortical connectivity during auditory language processing.…”
Section: Discussionmentioning
confidence: 82%
“…Alternatively, as a control of DCM overfitting, the hidden source was replaced by the CG [0,36,28]. Regions were interconnected with forward, backward, and lateral connections as described by David et al (2005David et al ( , 2006.…”
Section: Methodsmentioning
confidence: 99%